FOREIGN COMMUNICATIVE COMPETENCE AS A FACTOR OF PERSONAL DEVELOPMENT - Serdiuk, Liudmyla; Chykhantsova, Olena; Baranauskienė, Ingrida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Life in Ukraine has provided people with diversity and possibility in communication with the corresponding increase in intercultural communication. Therefore, foreign language teaching and learning at the universities should not only be instrumental, but it should set a new goal to train students with intercultural communicative competence to meet the needs of our globalized world. The article deals with the role of foreign language communicative competence and the problem of forming foreign language skills in communication that influence on the development of the person in the process of education in higher education institutions. Communicative competence means having ‘a competence to communicate’. The aim of the article is to investigate the level of foreign language communicative competence of the individuals and its impact on personality development. We used such research methods as observation, interview and questionnaire, analysis of the results of communication and teaching of students in a foreign language, the author’s method of determining the level of foreign language mastering, the expert assessments method. The results of our study determined that communicative competence implies the appropriate skills, the formation of which is a prerequisite for learning a foreign language in the educational environment. The results of the experiment allowed us to establish the psychological specificity of the process of mastering a foreign communication. The communicative competence is considered as a factor of personal development in the process of effective mastering of foreign languages. The foreign communicative competence is a recent notion and there is no clear consensus about what it is. Sometimes this term is referred to as global competence, international competence, multicultural competence and so forth.